Meta Analisis Populasi Kuskus (Ailurops sp. & Strigocuscus sp.) dan Upaya Pelestarian Habitat Kuskus di Kepulauan Sulawesi - Egi Sudira; Innes Prameswary; Intan Aliyani; Ade Suryanda (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2023)
The cuscus is endemic to Sulawesi which now based on data from the IUCN has an endangered status caused by the destruction of the cuscus' natural habitat as well as poaching. This research was conducted to determine the natural habitat of the cuscus and conservation efforts to maintain the sustainability of the cuscus in Indonesia. This study uses a literature review method. The data obtained was then analyzed quantitatively by calculating a similarity index to find out the similarity of the cuscus habitat and finding solutions for conservation efforts that can be carried out. Based on the results of a literature review, it is known that cuscus can be found in the Sulawesi archipelago, at low, medium and high altitudes. This statement is reinforced by the results of calculating the similarity index which shows an index value of more than 0.50 for each observation location which indicates a fairly even distribution of cuscus. Meanwhile, efforts to preserve the existence of the cuscus are through efforts to appreciate the value of the existence of the cuscus as an endemic animal to Indonesia, taking part in protecting the cuscus' natural habitat and not engaging in poaching, and complying with Indonesian conservation regulations.